Exogenous FABP4 increases breast cancer cell proliferation and activates the expression of fatty acid transport proteins. Issue 1 (6th April 2016) - Guaita‐Esteruelas, Sandra; Bosquet, Alba; Saavedra, Paula; Gumà, Josep; Girona, Josefa; Lam, Eric W.‐F.; Amillano, Kepa; Borràs, Joan; Masana, Lluís
Abstract : Adipose tissue plays an important role in tumor progression, because it provides nutrients and adipokines to proliferating cells. Fatty acid binding protein 4 (FABP4) is a key adipokine for fatty acid transport. In metabolic pathologies, plasma levels of FABP4 are increased. However, the role of this circulating protein is unknown. Recent studies have demonstrated that FABP4 might have a role in tumor progression, but the molecular mechanisms involved are still unclear. In this study, we analysed the role of eFABP4 (exogenous FABP4) in breast cancer progression. MCF‐7 and MDA‐MB‐231 breast cancer cells did not express substantial levels of FABP4 protein, but intracellular FABP4 levels increased after eFABP4 incubation. Moreover, eFABP4 enhanced the proliferation of these breast cancer cells but did not have any effect on MCF‐7 and MDA‐MB‐231 cell migration. Additionally, eFABP4 induced the AKT and MAPK signaling cascades in breast cancer cells, and the inhibition of these pathways reduced the eFBAP4‐mediated cell proliferation. Interestingly, eFABP4 treatment in MCF‐7 cells increased levels of the transcription factor FoxM1 and the fatty acid transport proteins CD36 and FABP5. In summary, we showed that eFABP4 plays a key role in tumor proliferation and activates the expression of fatty acid transport proteins in MCF‐7 breast cancer cells. © 2016 Wiley Periodicals, Inc.